KONSEP E-LEARNING DALAM MENDUKUNG PEMBELAJARAN DI PERGURUAN TINGGI - Fernando B. Siahaan (Cakrawala - Jurnal Humaniora, 2012)
Learning by using the conventional method currently does not support towards improving thequality of student learning. Lecturers or academic staff have the primary function to perform thetransfer of knowledge while the student has the function to receive the knowledge. More passivenature of this cause problems such as teacher attendance is absolutely necessary, referencesources are limited, and time is very limited. The development of information and communicationtechnology in education in particular has given rise to e-learning methods as a solution to supportthe learning is done with conventional methods. The research method used in this study is to usethe study of literature and observations on the use of e-learning on the web eUniversiti managedby Romi Satrio Wahono. Utilization of e-learning can improve the quality of teaching was done bystudents including students become more active in seeking knowledge, the Internet provideslearning resources that students need, and the formation of learning communities among students.The conclusion of this research is the application of e-learning methods can improve the quality ofthe students in the learning process, e-learning is present as the conventional method ofsupporting the learning process rather than to replace it, and the application of e-learning is theprimary function is as a companion mahasisea lecturer in the search for knowledge, whilestudents are the main actors in the pursuit of knowledge.Key Word: learning, e-learning, Internet